2004
DOI: 10.1175/1520-0469(2004)061<0121:svotna>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic View of the North Atlantic Oscillation

Abstract: This article investigates the synoptic characteristics of individual North Atlantic Oscillation (NAO) events by examining the daily evolution of the potential temperature field on the nominal tropopause (the 2-PVU surface). This quantity is obtained from the National Centers for Environmental Prediction-National Center for Atmospheric Research (NCEP-NCAR) reanalysis dataset for the winter season. For both phases, the NAO is found to originate from synoptic-scale waves. As these waves evolve into the low-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
347
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 289 publications
(388 citation statements)
references
References 27 publications
34
347
2
5
Order By: Relevance
“…3c). This implicates that negative-phase NAO events observed in the real atmosphere looks like a meandering blocking flow (Berggren et al 1949;Benedict et al 2004;LLW).…”
Section: A Scatter Diagrams Of Negative-phase Nao Eventsmentioning
confidence: 75%
See 4 more Smart Citations
“…3c). This implicates that negative-phase NAO events observed in the real atmosphere looks like a meandering blocking flow (Berggren et al 1949;Benedict et al 2004;LLW).…”
Section: A Scatter Diagrams Of Negative-phase Nao Eventsmentioning
confidence: 75%
“…In a previous paper (Luo et al 2007, hereafter LLW), a weakly nonlinear model is proposed to account for the interaction between preexisting planetary-scale and synoptic-scale waves leads to an NAO event, a zonally localized dipole mode (Hurrell 1995b;Vallis et al 2004;Cash et al 2005). Results from this theoretical model are found to bear a striking resemblance to observed NAO events for the negative and positive phases (Benedict et al 2004). It is shown that the phase of the NAO event depends strongly upon whether the preexisting planetary waves and preexisting eddy forcing (PEF) from synoptic-scale waves have a matching spatial structure.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations